Quán triệt quan điểm phát triển của triết học Mác - Lênin trong nâng cao chất lượng hoạt động nghiên cứu, giảng dạy các môn lí luận chính trị và khoa học xã hội nhân văn tại Trường Đại học Cảnh sát Nhân dân, Thành phố Hồ Chí Minh - Trần , Nguyễn Sĩ Nguyên; Vũ , Hoàng Toàn (Tạp chí Giáo dục, 2021)
Researching, summarizing the trends of human thought, the classics of Marxism-Leninism have clearly identified two basic views on the development of humanity. It is the metaphysical and dialectical view of development. Thoroughly grasping the developmental perspective in perception and practical activities helps us have an objective view of the evolution, know how to plan for the development of things and phenomenon that compliant with the law. The article researches grasping the developmental perspective of Marxist-Leninist Philosophy in the process of improving the quality of research and teaching Political Theory and Humanities Social Sciences at the University of Police People, Ho Chi Minh city. Contributing to the general development goal of the People’s Police University, Ho Chi Minh city, the Faculty of Political theory and the Social science and humanities needs to continue to build and complete the development orientation of research and teaching activities in Politics, Social Science and Humanities.